Pandangan Tentang Kecemburuan Allah dalam Hukum Kedua Dihubungkan dengan Ikatan Keluarga - Juwinner Dedy Kasingku; Sara Abigail Mononege; Alan Hubert Frederik Sanger (Journal on Education, 2023)
This article is a literature study that describes the concept of jealousy towards family, especially spouses and jealousy of God which is written in the Book of Exodus. To be understood, the author presents various information through related sources related to the topic and then explained descriptively. From the research that has been made, the concept of jealousy of a partner is different from the concept of jealousy of God based on general and Biblical views. Human jealousy can make it possible to sin and have some form of jealousy, whether at a young or old age, you will not be separated from this type of emotion. God's law helps human to reflect and breaking the law means not loving God. The Creator of mankind wanted His creation not to turn its back on the idols of the world. He cares about human; therefore, the law helps human not to sin, in this case helping human to obey so that there is no jealousy that will result in evil deeds against others and sins against God.